FAKTOR-FAKTOR YANG MEMPENGARUHI GIZI KURANG PADA BALITA DI PUSKESMAS SIDOMULYO - Aldinda, Tharra Widadari; Zalni, Rummy Islami; Halimah, Siti; Gandi, Putri Indra; Wahyuni, Diana Rifka; Pramita, Heni (Ensiklopedia of Journal, 2024)
Abstract: Toddlers are a group that is prone to experiencing nutritional problems. Nutritional problems are directly caused by insufficient intake and high levels of infectious diseases. This study aims to find out the factors related to malnutrition in toddlers in the working area of the Sidomulyo Health Center. The design of this study is an analytical survey research with a cross sectional approach. The research location is in the working area of the Sidomulyo Health Center. The research was conducted from January to June 2024. The population of this study is children under five. The sample was 95 people, data analysis was carried out by univariate and bivariate analysis. The results of the study with the chi-square test showed that there was a relationship between knowledge (p = 0.004), education (p = 0.000), birth distance (p = 0.000), and history of infectious diseases (p = 0.000) with malnutrition in toddlers in the Sidomulyo Health Center Working Area. The conclusion is that there is a relationship between knowledge, education, birth distance, and history of infectious diseases and malnutrition in toddlers in the Sidomulyo Health Center Working Area. It is hoped that health workers will further improve health promotion as their role to achieve a goal, namely improving maternal and child health.Keywords: Malnutrition, Toddlers